2020
DOI: 10.1101/2020.12.08.415505
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thiol drugs decrease SARS-CoV-2 lung injuryin vivoand disrupt SARS-CoV-2 spike complex binding to ACE2in vitro

Abstract: Coronavirus disease 2019 (COVID-19) is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and the SARS-CoV-2 spike protein is an envelope glycoprotein that binds angiotensin converting enzyme 2 as an entry receptor. The capacity of enveloped viruses to infect host cells depends on a precise thiol/disulfide balance in their surface glycoprotein complexes. To determine if cystines in the SARS-CoV-2 spike protein maintain a native binding interface that can be disrupted by drugs that clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 76 publications
3
22
0
2
Order By: Relevance
“…Instead, L452, together with F490 and L492, form a hydrophobic patch on the surface of the spike RBD (Figure 4A). To understand the effects of L452R RBD mutation on viral entry, pseudoviruses carrying D614G with L452R or W152C, or D614G alone were generated and used for infection of 293T cells stably expressing the ACE2 cell entry receptor and TMPRSS2 cofactor for SARS-CoV-2 (Hoffmann et al, 2020;Khanna et al, 2020). We See also Tables S1 and S5.…”
Section: Increased Transmissibility and Infectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, L452, together with F490 and L492, form a hydrophobic patch on the surface of the spike RBD (Figure 4A). To understand the effects of L452R RBD mutation on viral entry, pseudoviruses carrying D614G with L452R or W152C, or D614G alone were generated and used for infection of 293T cells stably expressing the ACE2 cell entry receptor and TMPRSS2 cofactor for SARS-CoV-2 (Hoffmann et al, 2020;Khanna et al, 2020). We See also Tables S1 and S5.…”
Section: Increased Transmissibility and Infectivitymentioning
confidence: 99%
“…Cells used for this study include Vero E6 cells, Vero-81 cells, Vero cells overexpressing human TMPRSS2 (Vero-TMPRSS2), A549 cells stably expressing ACE2 (A549-ACE2), and 293T cells stably expressing ACE2 and TMPRSS2 (293T-ACE2-TMPRSS2) (Khanna et al, 2020).…”
Section: Cell Culture Modelsmentioning
confidence: 99%
“…Other mechanisms could be involved in a potential beneficial effect of dalcetrapib in the prevention of SARS-CoV-2 infection. Indeed, two cysteine residues, Cys480 and Cys488, of the viral spike protein have been recently shown to be important for the binding of the spike protein to the ACE2 receptor, 32 and thiol-reactive substances including dalcetrapib (JTT-705) have shown to inhibit this important interaction and prevent syncytia formation and viral entry into cells. 33 Hati and Bhattacharyya 34 showed that the redox status plays an important role in the stability of key disulfide bonds present in both the spike protein and the ACE2 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Polyclonal cell populations were selected via fluorescence-activated cell sorting (FACS) as described below. The HEK293T cell line expressing ACE2 and TM-PRSS2 was generated as previously described 57 .…”
Section: Generation Of Stable Cell Linesmentioning
confidence: 99%